In Vitro Meat and Science Fiction: Contemporary Narratives of Cultured Flesh. Issue 2 (1st July 2022) - Castle, Nora
Abstract : This article argues that the in vitro (i.e., lab-grown) meat boom can be better understood by framing it within sf studies, both historically and especially through to the contemporary moment. Not only does in vitro meat (IVM) have a long history of representation in sf, it is also framed in the public and corporate spheres through the use of sf tropes. The article offers close readings of IVM in Margaret Atwood's Oryx and Crake (2003), Elizabeth Dougherty's The Blind Pig (2010), and director Brandon Cronenberg's Antiviral (2012), arguing that reading IVM in contemporary sf is a particularly effective method of thinking through its material effects.